OPTIMALISASI KEDUDUKAN, TUGAS POKOK, DAN FUNGSI PENGAWAS PENDIDIKAN AGAMA ISLAM (PAI) - MUSBAHAERI, MUSBAHAERI (DIDAKTIKA, 2017)
Supervisors of Islamic Education (PAI) have a very important role in improving the quality of education both in terms of process and output. Its position as supervisor of PAI subjects in schools to support the implementation of the PAI teacher's duties. The main task is to plan supervision, foster, monitor, and assess the implementation of learning PAI, and prepare supervisor report. Function as a supervisor to carry out academic supervision for teachers PAI. The results of supervision will be the evaluation material to carry out the guidance of PAI teachers. Given the importance of the PAI supervisory duties, it is deemed necessary to optimize the position, the main duty and function so that the PAI supervisor is not considered an unnecessary position. This optimization involves enhancing local government and ministerial cooperation in managing the division of supervisory tasks, developing the profession of PAI supervisors, and making PAI supervisors the first priority to be equipped with the latest knowledge and information related to Islamic religious education.